The Effect of Using PowerPoint Toward Teaching Writing Analytical Exposition at XI Grade of SMA Negeri 3 Jambi City Academic Year 2018/2019 - Yessy Nia; Khidayatul Munawwaroh (JELT: Journal of English Language Teaching, 2019)
The purpose of this research is to find out the language learning strategies that students used and to observe their achievement based on the strategies at second grade on SMAN 8 Kota Jambi Academic Year 2018/2019. The method used in this research is descriptive qualitative. The sample of this research is XI IPS 1 consists of 36 students, in order to get the sample in this research by using simple random sampling. The data are collected by using questionnaire adapted from Oxford (1990) and documentation from English teacher. The result of this research showed that there are very high students and high students in using language learning strategies. Based on the data, the most frequency strategies that students used are metacognitive strategies are used by 13 students (36%) with the average score very high (84,3), affective strategies are used by 9 students (25%) with the average score very high (84,1),social strategies are used by 6 students (17%) with the average score very high (82,2), and cognitive strategies are used by 3 students (8%) with the average score high (78,5), while the lowest frequency strategies that students used are memory strategies used by 4 students (11%) with the average score very high (81,6). Lastly, compensation strategies are used by 1 student (3) with the score high (78).Keywords: Learning Strategies, Achievement.